The Essential World History : Volume II: Since 1500 - Duiker, William J.; Spielvogel, Jackson J. (Boston, Massachusetts : Wadsworth, Cengage Learning, 2014)
For several million years after primates first appeared on the surface of the earth, human beings lived in a small communities, seeking to survive by hunting, fishing, and foraging in a frequently hostile environment. Then suddenly, in the space of a few thousand years, there was an abrupt change of direction as human beings in a few widely scattered areas of the globe began to master the art of cultivating food crops.
Part III. the emergence of new world patterns -- Part IV. modern patterns of world history -- Part V. toward a global civilization? the world since 1945.
Includes index.
Keywords: WORLD HISTORY